Interest Groups in American Politics: Pressure and Power - Nownes, Anthony J. (New York: Routledge, 2023)
Americans rail against so-called special interests but at the same time many members of society are themselves represented in one form or another by organized groups trying to affect the policymaking progress. This concise but thorough text demonstrates that interest groups are involved in the political system at all levels of government - federal, state, and local - and in all aspects of political activity, from election campaigns to agenda setting to lawmaking to policy implementation. Rather than an anomaly or distortion of the political system, it is a normal and healthy function of a pluralist society and democratic governance. Nonetheless, Nownes warns of the dangers of unwatched interest group activity, especially in the realms of the electoral process and issue advocacy. Interest Groups in American Politics, Second Edition, is grounded by the role of information in interest group activity, a theme that runs through the entire book. This much anticipated revision of Nownes's text retains a student friendly tone and thoroughly updates the references to interest group research, as well as adds a new chapter on the connections between interest groups and political parties. Numerous figures and tables throughout the book help students visualize important trends and information.